Model Kurikulum Terintegrasi: Reformulasi dan Aktualisasi pada Mata Kuliah Dasar-dasar Sains Islami - Basri, Hasan; Sari, Maimun (LITERATUS, 2024)
Reformulation and actualization of the integrated curriculum has become one of the characteristics of every State Islamic University. However, conceptually the terminology for integrating science and curriculum has not yet reached an agreement among experts. Even now, it is still a discourse that has not ended. This research tries to reveal two main problems: first, how the integrated curriculum is applied in the learning process of the basics of Islamic science in the chemistry education study program. Second, the extent to which the application of the integrative curriculum is appropriate in relation to learning the basics of Islamic science in the chemistry education study program. This research uses a qualitative descriptive-analysis approach with purposive sampling consisting of head of the study program, 2 lecturers, 5 students from unit 01 and 5 students from unit 02 in semester 2 (two) who took the basics of Islamic science course in the Chemistry Education Study Program. Data were collected using direct observation techniques, in-depth interviews, and document studies and questionnaires. The data analysis technique goes through the stages of data reduction, data presentation, data processing and interpretation and drawing conclusions (verification). The research results show that the implementation of the integrated curriculum in the basics of Islamic science courses has been realized at the planning and presentation stage of integrated content in line with CPL and the material taught in class is in sync with CPMK and RPS. Meanwhile, the model used is an integration model based on monotheism and fiqh. At the implementation stage in unit 01 the lecturer did not carry out apperception. Meanwhile, in unit 02 the lecturer begins learning by praying together, and after that the lecturer conducts an apperception and explores the students' learning experiences. The suitability of the curriculum implemented in the Chemistry Education Study Program with the integrated curriculum in the Basics of Islamic Science course has been realized adequately although it still needs improvement. It is hoped that the results of this research will become an initial reference for lecturers, observers and educational policy makers.